Analyzing uncertainty in projections of Canadian energy use and production: Results and insights from EMF 34 scenarios. (January 2021) - Hansen, Matthew; Bhargava, Abha; Nadew, Michael; Stogran, Melanie; Hansen, Lukas; Hundal, Mantaj; Budgell, Peter; Safton, Ryan
Abstract: This paper analyzes the uncertainty associated with Reference Case, or baseline, projections of Canadian energy use and production. We use the Canada Energy Regulator's Energy Futures modeling system to explore the impacts of changing key assumptions. The choice of assumptions and magnitude of change are guided by the scenarios in the Energy Modeling Forum (EMF) 34 project. We find important variations across all scenarios. In particular, we note that Canada's role as an energy producer is important for interpreting projection and scenario results. Overall, this analysis shows that it is important to test key assumptions in a typical Reference Case projection. However, this analysis also highlights many complexities in energy system modeling. It is also important to consider the potential interplay between key variables. This speaks to the importance of broader scenario analysis, where multiple assumptions are changed in an internally consistent way, as a useful complement to the focused scenario analysis found in this paper. Highlights: Canada's role as an energy producer is important for understanding projections. The Low Oil Price scenario has the lowest energy use outlook of those analyzed. The EMF34 scenarios provide a diverse range of outcomes for Canadian energy. Testing key assumptions in Reference projections of supply and demand is important. Scenarios focused on production show the largest changes from the Reference.